Eksperimentasi Peran Serat Alam Pada Tanah Lempung Dalam Upaya Peningkatan Infiltrasi Dan Plastisitas Tanah - Nurnawaty; Abd Rakhim Nanda; Tendri Ajeng; Intan Fadillah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Clay soil consists of a type with limited load-bearing ability and low shear strength, thus it is essential to enhance the soil's stability, as this is influenced by the moisture level. The amount of water obtained by the soil depends on the soil's ability to absorb and channel the water received from the soil surface to the lower layers. Therefore, alternative materials are needed to improve the properties of the soil. This study aims to determine the effect of adding natural fibers on the infiltration and plasticity of clay soil. This research was a laboratory based testing, where infiltration testing was carried out using channel media and soil stability testing using the Atterbeg method. The addition of natural fibers to clay soil affects the infiltration discharge. The highest infiltration discharge is clay soil with the addition of rice husks and the lowest infiltration discharge is clay soil with a mixture of coconut fiber. Adding rice husks to clay soil can reduce the plastic index number which is 6%.